القواعد القرآنية في تربية الذرية: (The Qur’anic Principles in Educating Children) - (Hessah Hamad Mohammed Alhawas), حصة بنت حمد محمد الحواس (At-Tajdid - Intellectual Refereed Journal, 2022)
Abstract It is a well-known fact to those who are concerned with the situation of muslim generation that there must be a true esrablished principles in education that need to be followed. They have been sterssing on this aspect in the forms of advice, instructions, and writings. The holy Qur’an itself is overflowed with educational pronciples but still awaits to be explained and informed to the society. The holy Qur’an contains ample principle for living that needs to be replicated against the widespread practice of many muslim societies to adopt the western educationa theories. Since these theories are the results of the human thinking, they only make their situations worse. There is such a difference between the fruits of human thought and the revelation from the Creator who is all knowing and wise. What is set forth in the holy Qur’an is in tandem with the nature of human. Hence, there is a need to deduce the pronciples from this source to fulfill the needs of our younger generation to enable them to stand on their feet to and become useful individuals. The study relies on the deductive method to explain the importance of children education, the justifications to tackle the issue and the wish of the Creator for good education for the younger generation. Keywords: Education, development, the holy Qur’an, Principles of education